2007
DOI: 10.1111/j.1600-0404.2007.00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating interleukin-15 and RANTES chemokine in Parkinson’s disease

Abstract: Our findings may suggest a recruitment of activated monocytes, macrophages and T lymphocytes to sites of inflammation in the central nervous system of PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 43 publications
4
56
1
1
Order By: Relevance
“…In vivo imaging studies of PD patients showed progressive microglial activation that was associated with the loss of dopaminergic neurons [39,40,41], as well as higher levels of proinflammatory cytokines in serum and CSF [42,43]. The loss of dopaminergic neurons in the substantia nigra has a direct effect on motor function; thus, the degree of microglial activation in neuroinflammation significantly contributes to the progression of motor dysfunction in PD patients [44].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo imaging studies of PD patients showed progressive microglial activation that was associated with the loss of dopaminergic neurons [39,40,41], as well as higher levels of proinflammatory cytokines in serum and CSF [42,43]. The loss of dopaminergic neurons in the substantia nigra has a direct effect on motor function; thus, the degree of microglial activation in neuroinflammation significantly contributes to the progression of motor dysfunction in PD patients [44].…”
Section: Discussionmentioning
confidence: 99%
“…Those microglial factors found in the brain, cerebrospinal fluid (CSF), and peripheral blood include transforming growth factor beta (TGFb), IL-1 alpha/beta (IL-1a/b), IL-6, IL-10, IL-12, IL-23, and TNF-a, many chemokines (RANTES/CCL5, MCP-1/CCL2, and IP-10/ CXCL10), proteolytic enzymes, matrix metalloproteinases, complement, growth factors, and glutamate (Griffin et al 1989;Dickson et al 1993;Moore and Thanos 1996;Qiu et al 1997). Moreover, COX-2 is present as increased levels of TRAF family member-associated NFkB activator (TANK) and NFKB1 in the SN, and IL-15, RANTES, and IL-10 levels are significantly elevated in brains and peripheral circulation in PD patients (Blum-Degen et al 1995;Teismann et al 2003;Rentzos et al 2007Rentzos et al , 2009Reynolds et al 2008a). Furthermore, innate immunity regulates lymphocyte infiltration into the CNS.…”
Section: Cross-regulation Of Adaptive and Innate Immunity In The Cnsmentioning
confidence: 99%
“…Early autopsy evidence within the SN of PD patients showed increased numbers of CD8 þ T cells in close proximity to activated microglia and degenerating neurons (McGeer et al 1988a (Baba et al 2005), whereas circulating IL-15, RANTES, and IL-10 are significantly elevated in PD patients compared with controls (Rentzos et al 2007(Rentzos et al , 2009). Evidence of increased mutual coexpression of CD4 and CD8 by CD45R0 þ T cells, increased expression of CD25 (a chain of the high-affinity IL-2 receptor) and TNF-a receptors, and diminished expression of IFN-g receptors suggest that these T-cell subsets from PD patients are indeed activated.…”
Section: Inflammation and Immunity In Parkinson's Diseasementioning
confidence: 99%
“…Increased levels of interleukin-10 and the chemokine RANTES (Regulated on Activation, Normal T cell Expressed and Secreted) have been found in serum collected from individuals with PD compared with controls. 50 Elevated tumor necrosis factor (TNF)-α levels have been detected in association with PD in both plasma and CSF. 51,52 Abnormal antibody expression associated with PD includes CSF antineuronal antibodies, 53 anti-α-synuclein antibodies, 29,31 and antimelanin antibodies.…”
Section: Markers Of Disrupted Inflammatory Pathwaysmentioning
confidence: 99%